Dukhovnaia zhizn' pervobytnogo obshchestva - A. F. Anisimov. (Izdatel'stvo "Nauka", 1966)
At head of title: Akademiia nauk SSSR. Ministerstvo kul'tury RSFSR. Muzei istorii religii i ateizma.Includes bibliographical references.